PEMETAAN SUHU PERMUKAAN AIR LAUT DAN KEASAMAN DI PESISIR PANTAI BALEKAMBANG DENGAN DATA CITRA SATELIT LANDSAT 8 - Pratista Shafa Brillian; Siti Zainab (LPPM Universitas Abdurrab, 2025)
Balekambang Beach is one of the beaches located in the southern part of Malang Regency, East Java Province. Most people on the beach work as fishermen and in the tourism sector. This research aims to provide new knowledge on the condition of Balekambang Beach in terms of sea surface temperature (SST) and seawater acidity (pH). In this study, the research method used was field data collection (in situ) and data collection from Landsat 8 satellite images for SPL and pH mapping with the help of the SeaDAS application. The best analysis result of satellite image data for SPL is satellite image data in Band 2. The SPL algorithm model is polynomial with y = 20.982ln(x) + 73.175 and R² value = 0.1904. The best analysis result of satellite image data for pH is satellite image data in Band 4. The pH algorithm model is linear with y = -13.601x + 8.3768 and R² value = 0.0026.